Hubungan Keterampilan Literasi Awal dengan Kemampuan Bahasa Ekspresif Tingkat Kata pada Anak Usia Prasekolah di RA Sunan Ampel Al-Jauhar Ngawi - Ikhwansyah, Fajar Nur; Mangunsong, Roy Romey Daulas (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: The education of children of preschool age is closely related to the development of children's literacy skills. The lack of readiness of early literacy skills will affect the child's success in communicating and speaking with their environment. Based on a survey conducted by the Program for International Student Assessment (PISA) released by the Organization for Economic Co-operation and Development (OECD) in 2019. Indonesia ranks 62nd out of 70 countries related to literacy rate, or is in the bottom 10 countries that have low literacy levels. Objectives: analyze the Corellation of Early Literacy Skills with Word-Level Expressive Language Skills in Preschool-Age Children at RA Sunan Ampel Al-Jauhar Ngawi. Methods: This study was a quantitative study using an observational analytic research design with a cross sectional approach. The sample size of this study was 32 respondents aged 3–6 years (preschool). The statistical test used in this study was the Kendall Tau test. Results: The Kendall's tau test results revealed that a significance value of 0.000 was obtained with corellation coefficient or a r value of 0.603 which means that the correlation value is strong and positive, so Alternative hypotheses is accepted. This means that there is a strong relationship between early literacy skills and word-level expressive language skills. The better the early literacy skills, the better the expressive language skills of children is, and vice versa. Conclusion: There is a strong and positive correlation between early literacy skills and expressive language skills in preschool children. Keywords: Early literacy skills, expressive language skills, preschoolers